Evolución del empleo y crecimiento económico en la ciudad de Machala, período 2010-2020. - Toledo Salas, Marcelo Andre; Moreno Loayza, Mateo Andres (Machala : Universidad Técnica de Machala, 2022)
This paper analyzes economic growth and employment in the city of Machala during 2010-2020. Therefore, the elasticity of employment was used to determine how it has evolved with respect to productivity. The elasticity of employment varies over time mainly due to economic conditions and the ability to solve the problem of not generating more employment. In addition, there were drawbacks to perform a double log econometric model such as it was not robust and the coefficients of the estimation were biased by standard errors generating distrust to determine its effects with the dependent variable full employment and the explanatory variables gross value added, current income and investment expenditures of the GAD of Machala during 2010-2019. For this reason, two double log econometric models were carried out in order to know how the explanatory variables such as current income and investment of the GAD of Machala have contributed to the dependent variables such as underemployment and Gross Domestic Product of Ecuador. These two loglog models were feasible according to the validation tests Jarque Bera, homoscedasticity, VIF. Finally, every 1% increase in investment decreases the rate of underemployment by 0.89% and for every 1% increase in current spending, underemployment is reduced by 1.56%. On the other hand, if 1% is allocated to investment, it contributes 0.23% to GDP and every 1% increase in current spending contributes 0.09% to GDP.
En el presente trabajo analiza el crecimiento económico y el empleo en la ciudad de Machala durante 2010-2020. Por lo cual se utilizó la elasticidad del empleo para determinar la manera que ha evolucionado respecto a la productividad. La elasticidad del empleo varía con el tiempo principalmente a las condiciones económicas y en la capacidad de solucionar la problemática en no generar más empleo. Además, hubo inconvenientes al realizar un modelo econométrico doble log como por ejemplo que no era robusto y los coeficientes de la estimación estaba insesgado por los errores estándar generando desconfianza para determinar sus efectos con la variable dependiente el empleo pleno y las variables explicativas valor agregado bruto, ingresos corrientes y gastos de inversión del GAD de Machala durante 2010-2019. Por tal razón se realizó dos modelos econométricos doble log con la finalidad de conocer la manera que han contribuido las variables explicativas como ingresos corrientes y de inversión del GAD de Machala respecto a las variables dependientes como Subempleo y Producto Interno Bruto del Ecuador. Estos dos modelos loglog realizados fueron factibles acorde a los test de validación tanto Jarque Bera, Homocedasticidad, VIF. Por último, cada 1% que se destine a la inversión la tasa del subempleo disminuye 0.89% y por cada 1% de incremento en gasto corriente se reduce 1.56% al subempleo. En cambio, si se destina 1% en la inversión contribuye 0.23% al PIB y cada 1% en gasto corriente aporta 0.09% al PIB.
Keywords: CRECIMIENTO ECONOMICO; EMPLEO; ELASTICIDAD DEL EMPLEO